Metabolic roles of inorganic polyphosphates in chlorella cells - Miyachi, Shigetoh; Kanai, Ryuzi; Mihara, Sayoko; Miyachi, Shizuko; Aoki, Shigeji (Biochimica et biophysica acta, 1964)
1. 1. A new type of inorganic polyphosphate (poly-P i) was detected in Chlorella cells and named Poly-P i “D”. It is extractable with 2 N KOH at 37° together with Poly-P i “C” which has been reported earlier. Upon neutralization of the extract with perchloric acid, Poly-P i “C” is co-precipitated with perchloric acid while Poly-Pi “D” remains dissolved. 2. 2. Using uniformly 32P-labeled Chlorella cells which are subjected to various environmental conditions, the metabolic role of Poly-P 1 “D”, as well as those referred to earlier as Poly-P i's “A”, “B” and “C” were investigated. 3. 3. On incubating the 32P-labeled algal cells in a phosphate-free medium under photosynthetic conditions, ribonucleic acid increased and Poly-P i “D” decreased. When the 32P-labeled algal cells were subcultured in the normal “cold” medium under photosynthetic conditions, a large amount of external phosphate but only a small amount of endogenous 32P was incorporated into the ribonucleic acid fraction. In the meantime, the 32P in Poly-P i's “C” and “A” decreased considerably while that in Poly-P i's “B” and “D” decreased slightly or remained constant. It has been reported that deoxyribonucleic acid and phosphoprotein increased with contamitant decrease of Poly-P 1's “A”, “B” and “C” in a phosphate-free medium under photosynthetic condition, and that 32P in the fractions of deoxyribonucleic acid and protein continued to increase when the 32P-labeled algal cells were subcultured in the normal “cold” medium 1. It was therefore, inferred that, under photosynthetic conditions, Poly-P i's “C” and “A” serve as intermediates in the transfer of phosphate to the phosphorus compounds synthesized such as deoxyribonucleic acid and phosphoprotein, while Poly-P i's “B” and “D” function as reservoirs of phosphate which are utilized only in the absence of exogenous phosphate source. 4. 4. In the dark the 32P in Poly-P i “A” continued to increase slowly both in the phosphate-free medium and in the normal cold medium, while no significant change was observed in the levels of 32P or total phosphate of the other phosphorus compounds. This suggests that Poly-P i “A” accepts phosphate—independently of light— from some intracellular phosphate source.